Prinsip Realitas Absolut dalam Teks Saivagama Nusantara - I Gede Suwantana (Sanjiwani: Jurnal Filsafat, 2021)
Saivagama is a teaching which refers to Siva as Absolute Reality. Saivagama Nusantara, namely the Saiva teachings that developed in Indonesia, describes Siva with various names and attributes, such as in the Bhuwana Kosa it is called Rudra, Vrhaspati Tattva calls it Ishvara, and various negation names such as sunya, paramasunya, paramasiva and others. Several Saiva Nusantara texts generally discuss the Absolute Reality into three main groups, namely the existence of the Absolute Reality (Siva), the emanation of the Absolute Reality, and the Reabsorption of the Absolute Reality. Existentially Siva is described as Nirguna and Saguna. In principle Siva is characterless. However, when the active principle of Himself brings creation, then Siva is both immanent and transcendent at the same time. While in creation, Siva was shackled by various factors related to the material aspect. Meanwhile, the reabsorption aspect of absolute Reality describes the pralaya aspect, where all elements are returned to their highest aspect. Every being born evolutionarily is directed towards this process of reabsorption.